Association between alterations of corneal sub-basal nerve plexus analyzed with in vivo confocal microscopy and long-term glycemic variability. Issue 5 (September 2021) - Pellegrini, Marco; Sebastiani, Stefano; Tucci, Lorenzo; Giannaccare, Giuseppe; Moscatiello, Simona; Laffi, Gilberto; Pagotto, Uberto; Di Dalmazi, Guido; Versura, Piera
Purpose: The effect of long-term glycemic variability upon corneal sub-basal nerve plexus (CSNP) morphology analyzed by in vivo confocal microscopy (IVCM) has been poorly investigated in the setting of type 1 diabetes mellitus (T1DM). Our purpose was to analyze the association between morphometric parameters of CSNP and new markers of glycemic variability in a population of patients with T1DM. Methods: Forty patients with T1DM underwent: assessment of diabetic neuropathy (DN); analysis of subcutaneous advanced glycated end-products; IVCM scans of CSNP. The fully automated software ACCMetrics was employed to analyze IVCM images and calculate seven corneal nerve parameters. Data of diabetes duration, mean and standard deviation (SD) of either last-year and all-time glycated hemoglobin (HbA1C ) were retrieved. Results: Diabetes duration and all-time SD of HbA1C were independently associated with CNFD (R = –0.26, p = 0.01; R = –0.27, p = 0.047 respectively), CNFL (R = –0.12; p = 0.01; R = –0.17, p = 0.01 respectively) and CNFrD (R = –0.001, p = 0.009; R = –0.002, p = 0.007 respectively). The analysis of the association among IVCM parameters and specific subtypes of DN showed that altered cold sensitivity was independently associated with CNFD (B = –0.24, p = 0.01), CNFL (B = –0.46, p = 0.01) and CNFrD (B = –28.65, p = 0.03). Conclusions: All-time SD of HbA1C and disease duration were found to be independent predictors of damage to CSNP in patients with T1DM.